Preparation and Properties of Nano-ZnO Combined with Biomass Heavy Oil Composite-Modified Asphalt - He Tao; Hongming Liu; Xiangbing Xie; Tao Sun; Ruipeng Dong; Xiaolu Lu (Advances in Materials Science and Engineering)
Biomass heavy oil is employed to partially substitute the petroleum-based asphalt due to its renewability, environmentally friendly, and cost-effective advantages. However, its usage weakens the high-temperature performance of petroleum asphalt. Therefore, nano-ZnO was employed as a modifier to make composite-modified asphalt to improve the high-temperature performance in this paper. It was prepared in two steps: first, bio-asphalt was prepared by adding biomass heavy oil based on a certain content of matrix asphalt and then adding nano-ZnO with the particle size of 20 nm. The modification methods of bio-asphalt and composite-modified asphalt were analyzed by Fourier infrared (FTIR) and X-ray diffraction (XRD) experiments. Three major indexes test, dynamic shear rheological test, Brookfield rotational viscosity test (RV), and thermogravimetric analysis (TG-DSC) are used to analyze the high-temperature performance of bio-asphalt and composite-modified asphalt. The results show that biomass heavy oil and nano-ZnO are used to physically and chemically modify asphalt and the modification effect of bio-asphalt is the best when the biomass heavy oil content is about 9%. The high-temperature performance of composite heavy oil-modified asphalt is improved significantly. The performance indexes of Bio-6% and 1% nano-ZnO composite-modified asphalt are better than bio-asphalt. However, the high-temperature performance of Bio-12% and 3% nano-ZnO composite-modified asphalt is the best.